Intrumentos de triagem auditiva em idosos: teste de dicótico de dígitos e questionário Speech, Spatial and Hearing - Almeida, Maiara Cristine Oliveira de (2023)
As there is a high prevalence of hearing loss in the elderly, much has been studied about hearing decline concomitant with cognitive changes in advanced age. The sooner hearing loss is identified, the sooner the use of a sound amplification device can be i ndicated and thus contribute to cognitive rehabilitation. Hearing screening enables an early hearing diagnosis and is a quick, effective and safe method for identifying possible hearing changes, forwarding them in a democratized manner and with equity in a ssistance. The goal of this research was to verify the accuracy of the software based Digits in Noise Test in Brazilian Portuguese and to analyze the findings of the Speech, Spatial walk Qualities ( questionnaire in elderly people. The s tudy was approv ed under opinion number 5,480,390 by the Research Ethics Committee of a public Federal University. This is a cross sectional observational analytical research, which has os its research instrument tonal and vocal audiometry, imitanciometry, application of the digits in noise test ( and the Speech, Spatial and Qualities of Hearing Scale ( in the version reduced with 12 items, in Brazilian Portuguese, associating these findings in a population of 134 elderly people. The number of stud participantes d as obtende usina the sampe sie calculai o for finita population jeans, with an alpha erro param éter qual to 0.05, standard devia í on of 9 µ V and toler á vel erro of 4 µV. The exames fere cá rie out no elderly people registre with a social associativo for the elderly in a municipalista in the skate of Alagoas. The resultas fere analyzed using the ROC curve and descriptive statistics, through graphs and tables, presenting sociodemographic data, correlation of pure tone audiometry with the results of the questio nnaire, analysis of frequencies and percentages, average and minimum and maximum values. 145 initial assessments were carried out, in which nine subjects were excluded for not having obtained a minimum score of 25 points in the mini mental and two for not being able to complete the exams, totaling in the end 134 subjects participating in the research. The average age was 69.56 years. The TDR speech recognition threshold of the total sample of subjects had an average of 9.74dB. As a result, the pass/fail cr iterion of the test under study finds its cutoff point at an average signal to noise ratio ( of 10.9dB and shows a sensitivity value of 80% and specificity of 62.7%. The final mean signal to noise ratio ( was more positive in individuals with grea ter hearing loss and more negative in individuals with normal hearing. The SSQ questionnaire did not show good accuracy, however there were significant differences between the normal hearing group and those with hearing loss. Elderly people with hearing lo ss have more positive recognition threshold values in noise when compared to the group without loss. As for the SSQ, the average of all skills in the group with hearing loss has reduced scores when compared to those without hearing loss. The TDR and is sensitive for detecting hearing loss while SSQ can be used as a complementary test.